Burst-Switched IP Over DWDM Networks: Design And Analysis - Abdelouahab, Abid (2007)
In this thesis, a detailed survey on WDM Burst Switching is provided. Burst Switching network architecture, burst assembly, signaling and reservation protocols; QoS support and contention resolution techniques are discussed.